Question
upstudy study bank question image url

Q4. (i) Find the exact solution of the equation \[ 8^{2 x+1}=6 \] giving your answer in the form \( a+b \log _{2} 3 \), where \( a \) and \( b \) are constants to be found. (ii) Using the laws of logarithms, solve \[ \log _{5}(7-2 y)=2 \log _{5}(y+1)-1 \]

Ask by Reyes Martinez. in Qatar
Feb 17,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(i) \( x = -\frac{1}{3} + \frac{1}{6} \log_{2} 3 \) (ii) \( y = -6 + \sqrt{70} \)

Solution

We solve each part step by step. ───────────────────────────── Part (i) We need to solve   8^(2x + 1) = 6 Step 1. Express 8 as a power of 2. Since 8 = 2³, we can rewrite the left side:   (2³)^(2x + 1) = 2^(3(2x + 1)) = 2^(6x + 3). Thus the equation becomes   2^(6x + 3) = 6. Step 2. Take logarithms with base 2 of both sides:   6x + 3 = log₂6. Step 3. Solve for x:   6x = log₂6 – 3   x = (log₂6 – 3) / 6. Step 4. Write log₂6 in a form that involves log₂3. Note that 6 = 2 × 3, so   log₂6 = log₂2 + log₂3 = 1 + log₂3. Substitute back:   x = (1 + log₂3 – 3) / 6 = (log₂3 – 2) / 6. This can be rearranged to emphasize the required form a + b·log₂3:   x = –2/6 + (1/6)·log₂3 = –1/3 + (1/6)·log₂3. Thus, the constants are a = –1/3 and b = 1/6. ───────────────────────────── Part (ii) We need to solve   log₅(7 – 2y) = 2·log₅(y + 1) – 1. Step 1. Use the logarithm laws. Express the right-hand side as a single logarithm. Notice:   2·log₅(y + 1) = log₅((y + 1)²). Also, recall that subtracting 1 is equivalent to subtracting log₅5 because log₅5 = 1. Hence,   2·log₅(y + 1) – 1 = log₅((y + 1)²) – log₅5 = log₅[(y + 1)²/5]. So the equation becomes   log₅(7 – 2y) = log₅[(y + 1)²/5]. Step 2. Equate the arguments (the expressions inside the logarithms) provided they are positive:   7 – 2y = (y + 1)² / 5. Step 3. Multiply both sides by 5:   5(7 – 2y) = (y + 1)²   35 – 10y = y² + 2y + 1. Step 4. Rearranging to set the quadratic to zero:   0 = y² + 2y + 1 + 10y – 35   0 = y² + 12y – 34. This is the quadratic equation:   y² + 12y – 34 = 0. Step 5. Use the quadratic formula, y = [–b ± √(b² – 4ac)] / (2a), where a = 1, b = 12, and c = –34:   Discriminant: Δ = 12² – 4(1)(–34) = 144 + 136 = 280. Thus,   y = [–12 ± √280] / 2. Since √280 = 2√70, then   y = [–12 ± 2√70] / 2 = –6 ± √70. Step 6. Check the domain restrictions. For the logarithms we need:   a) y + 1 > 0 ⟹ y > –1,   b) 7 – 2y > 0 ⟹ y < 7/2 = 3.5. Evaluate both solutions:   • y = –6 – √70 is much less than –1 (and thus invalid).   • y = –6 + √70. Since √70 ≈ 8.37, we get y ≈ 2.37, which satisfies y > –1 and y < 3.5. Thus the unique solution is   y = –6 + √70. ───────────────────────────── Final Answers (i) x = –1/3 + (1/6)·log₂3   (with constants a = –1/3, b = 1/6) (ii) y = –6 + √70.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation \( 8^{2x+1}=6 \), we can rewrite it using base 2: since \( 8 = 2^3 \), we have \[ (2^3)^{2x + 1} = 6 \implies 2^{6x + 3} = 6. \] Taking logarithms of both sides, we get \[ 6x + 3 = \log_2 6 \implies 6x = \log_2 6 - 3 \implies x = \frac{\log_2 6 - 3}{6}. \] Now, \( \log_2 6 \) can be expressed as \( \log_2 (2 \cdot 3) = \log_2 2 + \log_2 3 = 1 + \log_2 3 \). Substituting this into our expression for \( x \): \[ x = \frac{(1 + \log_2 3) - 3}{6} = \frac{\log_2 3 - 2}{6} = -\frac{1}{3} + \frac{1}{6} \log_2 3. \] Thus, in the form \( a + b \log_2 3 \), we find \( a = -\frac{1}{3} \) and \( b = \frac{1}{6} \). --- For the logarithmic equation \( \log_{5}(7-2y)=2 \log_{5}(y+1)-1 \), we can first rewrite the right side. Using properties of logarithms, \( 2 \log_{5}(y+1) \) can be expressed as \( \log_{5}((y+1)^2) \). Thus, we have: \[ \log_{5}(7-2y) = \log_{5}((y+1)^2) - 1. \] Now, recall that subtracting 1 is equivalent to dividing by 5: \[ \log_{5}(7-2y) = \log_{5}\left(\frac{(y+1)^2}{5}\right). \] If we drop the logs (since the bases are the same), we find: \[ 7 - 2y = \frac{(y+1)^2}{5}. \] Multiplying both sides by 5 results in: \[ 5(7 - 2y) = (y + 1)^2. \] This simplifies to: \[ 35 - 10y = y^2 + 2y + 1, \] which can be rearranged to form a quadratic equation: \[ y^2 + 12y - 34 = 0. \] Using the quadratic formula \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ y = \frac{-12 \pm \sqrt{12^2 - 4 \cdot 1 \cdot (-34)}}{2 \cdot 1} = \frac{-12 \pm \sqrt{144 + 136}}{2} = \frac{-12 \pm \sqrt{280}}{2}. \] Simplifying, we find: \[ y = \frac{-12 \pm 2\sqrt{70}}{2} = -6 \pm \sqrt{70}. \] Thus, the solutions to the equation are: \[ y = -6 + \sqrt{70} \quad \text{or} \quad y = -6 - \sqrt{70}. \] Only \( -6 + \sqrt{70} \) is a valid solution since \( y \) must satisfy \( y+1 > 0 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy